Advances in human factors in robots and unmanned systems : proceedings of the AHFE 2017 International Conference on Human Factors in Robots and Unmanned Systems, July 17−21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA /: proceedings of the AHFE 2017 International Conference on Human Factors in Robots and Unmanned Systems, July 17−21, 2017, The Westin Bonaventure Hotel, Los Angeles, California, USA. ([2018]) - Unknown
No abstract available